Cimatti Field – An example of using seismic amplitude to determine in-place resource. Issue 1 (1st December 2019) - Micenko, Michael
Summary: The Cimatti oil field is located in the Exmouth sub-basin offshore Western Australia. The area has good 3D seismic coverage and the Jurassic Macedon Member reservoir is associated with an anomalously high seismic amplitude. These anomalous amplitudes can be used to estimate the thickness of the reservoir sand. The Cimatti-1 well was drilled in November 2010 and intersected a 15.4m TVD column of high net-gross, oil saturated sand. No oil-water contact was observed. An appraisal sidetrack (Cimatti-2) followed immediately with the aim of testing a downdip area near the edge of the field to the northwest. Cimatti-2 deliberately targeted an area with about half the seismic amplitude of the discovery and intersected a 6.8 m TVD of oil saturated sand. Mapping, engineering and economic studies were carried out following the discovery and in 2018 a drilling program of production and injection wells commenced. The tuning thickness of the wavelet extracted from the seismic data is 22 m. Mapping of the top and base reservoir reflections indicates that the reservoir thickness across the field is less than the tuning thickness. In such a case the seismic amplitude is related to net sand thickness. A linear relationship between bed thickness and seismic amplitude was established using the two data points (Cimatti-1 and Cimatti-2) and a sand thickness map of the field was produced. This map was then used to calculate an estimated in-place resources above an assumed oil-water contact. During development drilling in 2018 Schlumberger's Geosphere tool was used to determine the position of the near horizontal well bore relative to the top and bottom of the reservoir and hence the sand thickness could be estimated. These Geosphere based estimates were made at several places along the well paths and confirmed the amplitude – thickness relationship derived from the near vertical wells several years earlier.